DEMOKRATISASI DAN HAK ASASI MANUSIA DI PEDESAAN INDONESIA: ANALISIS EKSKLUSI SOSIAL, ELITE CAPTURE, DAN MODAL SOSIAL PETANI KOPI SEMENDE MUARA ENIM - Selvita Andriani; Henni Martini; Mira Shintia; Jose Daniel Vargas Rodriguez; Rudy Kurniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research investigates the complex intersection of democratization, human rights, and agrarian dynamics in rural Indonesia, specifically focusing on smallholder coffee farmers in the Semende region, Muara Enim Regency. Despite the formalization of village autonomy through Law No. 6 of 2014, substantive democracy at the grassroots level remains constrained by persistent elite capture and systemic social exclusion. Utilizing a qualitative systematic review (SLR) and secondary data from Statistics Indonesia (BPS), this study reveals that procedural democratization does not automatically translate into the realization of socio-economic human rights. Agrarian conflicts and asymmetrical supply chains marginalize local farmers. To counter these forces, the research highlights the strategic role of social capital through the Tunggu Tubang matrilineal system. By leveraging collective norms, communities can develop alternative models like the "Collective Coffee Barn" to mitigate elite dominance. The report argues that true democratization necessitates a shift toward inclusive governance that integrates indigenous knowledge.